Contrastive analysis of Turkish and English in Turkish EFL learners’ spoken discourse - Yildiz, Mustafa (International Journal of English Studies, 2016)
The present study aimed at finding whether L1 Turkish caused interference errors on Turkish EFL learners’ spoken English discourse. Whether English proficiency level had any effect on the number of errors learners made was further investigated. The participants were given the chance to choose one of the two alternative topics to speak about. The entire videotaped speaking session was further transcribed to analyze the spoken errors. The results indicated that prepositional, lexical, and grammatical errors were the most frequently encountered errors, in descending order. Also, independent samples t-test was applied to the data to determine whether English proficiency level had any effect on the number of errors made by two different English proficiency groups. It was found that there was no significant difference between two different English proficiency groups with regard to the number of errors they made.